The newborn behavioural observations (NBO) system embedded in routine postpartum care in at-risk families in Iceland: a randomised controlled trial - Lisbeth Valla; Kari Slinning; Tore Wentzel-Larsen; Gun-Mette Røsand; Stefanía Birna Arnardóttir (BMC Pregnancy and Childbirth)
Abstract Background The Newborn Behaviour Observation system (NBO) is a flexible relationship-based intervention designed to sensitise parents to their newborn’s capacities, to increase parental confidence and foster the bond between parent and infant. The aim of this study was to investigate the effects of an NBO intervention on maternal confidence during the first month postpartum, and on the quality of mother-infant interaction at infant age 4 months in a sample of mothers who exhibit elevated signs of distress or depression during pregnancy and/or describe prior experiences of mental health issues. Method Pregnant women with current emotional distress and/or a history of anxiety and depression were recruited from a healthcare centre in Reykjavik, between August 2016 and April 2018. The study used a two-group, randomised trial design with six measuring points, in which 54 women were randomly assigned to either the intervention or control group. The intervention group (n = 26) received the NBO in combination with standard care during routine home visits. The control group (n = 28) received the same numbers of home visits with standard care without NBO. Maternal confidence was measured using a parent questionnaire (covering learning outcomes relating to the infant’s communicative signals and maternal confidence) administered after each home visit in weeks 2, 3 and 4 postpartum. At 4 months infant age, a free-play situation involving mother-infant interaction was video-recorded in the participants’ homes and coded using the Emotional Availability Scale (EAS). Mixed effects models were used to estimate group differences in learning outcomes and maternal confidence across three time points. Two sample t-tests were used to compare the two groups’ EAS scores. Results The mothers in the intervention-group reported significantly higher maternal confidence and increased knowledge about their infant compared to the control group. Adjusted analyses suggest some evidence of a higher EAS non-hostility score in the intervention group (p = .031), but not for the other EAS scale scores (p ≥ .118). Conclusion Early home visits combining NBO with standard care enhance maternal confidence and the mother’s understanding of her infant. The small sample size makes it difficult to conclude whether repeated NBO sessions during the first month increase dimensions of maternal sensitivity in mother-infant interaction at 4 months postpartum. Trial registration ClinicalTrials.gov ID NCT04739332, Registered 02/01/2021.